Single-Stage Hybrid Arch Repair for Patients with Shaggy Aorta - Oishi, Yasuhisa; Kimura, Satoshi; Sonoda, Hiromichi; Shiose, Akira (AORTA, 2019)
Operating on extended arch aneurysms that contain severe atherosclerotic plaques is difficult. In such cases, the incidence of intraoperative multiple embolization is very high. We applied single-stage hybrid arch repair, which involved ascending aorta replacement and debranching of arch vessels, consecutively with endovascular repair for two patients. This technique was developed to prevent embolization of atherosclerotic plaques during cardiopulmonary bypass, and abrasion of the plaques during thoracic endovascular repair. Both patients recovered without embolic complications.
Keywords: arch aneurysm; shaggy aorta; hybrid operation